Mediatised performance and Theatre for Young People: How TYP is responding to Digital Natives. - Anderson, Michael (Caribbean Quarterly, 2007)
This paper explores how Theatre For Young People (TYP) has responded to the change in their audiences. As young peoples desires and preferences shift from generation to generation TYP companies are faced with the challenge of engaging new audiences and representing their voices in the content and form of TYP. This paper examines the myths that relate to mediated performance and examines how two TYP companies are using varied technologies to respond to their digital native audiences through performances with an increased and more integrated approach to and use of technology.